Studi Kepustakaan Profil Eritosit Ayam Broiler Dengan Pemberian Moringa Oleifera Lam. Sebagai Feed Additive - Paremadjangga, Rambu L.A; Novian, Dede Rival; Laut, Meity M. (Jurnal Veteriner Nusantara, 2024)
Broiler have a very fast growth rate, so that optimal production can be realized if their nutritional needs are sufficient. Erythrocytes are an indicator of adequate nutrition and nutritional value obtained by chickens through the feed they consume. This study aims to determine whether the addition of Moringa leaf meal in feed can affect the total erythrocyte, hemoglobin levels and hematocrit value of broiler. This study uses a literature study approach by searching and collecting data through Google Schoolar and Mendeley, then it is analyzed descriptively. Based on the results of the study, it was found that the addition of Moringa leaf meal in the feed had a good effect on increasing the number of erythrocytes values ​​ranging from 2,30 to 2,36 x 106/mm3; 2,01 to 3,41 x 106/mm3; 3,32 to 3,99 x 106/mm3; 3,07 to 3,81 x 106/mm3; 3,08 to 3,43 x 106/mm3; 2,78 to 3,54 x 106/mm3; 3,04 to 3,33 x 106/mm3; hemoglobin levels values ​​ranging from 9,54 to 11,12 g/dL; 8,80 to 13,90 g/dL; 8,72 to 9,73 g/dL; 5,53 to 7,99 g/dL; 13,73 to 14,83 g/dL; 8,20 to 9,70 g/dL; 9,92 to 10,25; and the hematocrit values ​​ranging from 24,10 to 27,30%; 29,00 to 44,00%; 29,91 to 31,79%; 16,67 to 24,00%; 35,13 to 37,93%; 17,77 to 28,10%; 29,76 to 30,77%. This is because Moringa leaf meal contains nutrients needed for the forming of erythrocytes (erythropoesis) such as protein, iron, vitamin B9 and vitamin B12, copper, and folic acid.